Assessment of the G2 model estimations and comparing it with erosion plots and observed sediment data in the Southern Caspian Sea river basins - Khadijeh Haji; Abdulvahed Khaledi Darvishan; Raoof Mostafazadeh (Journal of Hydrology: Regional Studies)
Study Region: The Caspian Sea basin covers the northern region of Iran with an area of 176,393.91 km2. Study Focus: Performance evaluation of the G2loss and G2sed model for estimating soil erosion and sediment yield, and comparing it with erosion plots and observed suspended sediment data obtained from SRCs, is a primary goal of this research. The G2 model input factors were prepared using meteorological data, satellite imagery, topographic, hydrographic and soil variables, and the utilization of GIS-RS techniques. Additionally, observed sediment data were developed for 32 sediment monitoring stations based on daily streamflow and sediment concentration data collected from 2001 to 2018. Subsequently, the observed suspended sediment compared with the estimated values from the G2sed model. New Hydrological Insights for the Region: The study found an annual average soil erosion rate of 11.24 t ha−1 in the study area. Rangelands exhibited the highest erosion rate at 16.87 t ha−1 yr−1. Sediment delivery ratios ranged from 0.04 to 0.28, resulting in an average annual sediment yield of 1.10 t ha−1. Peak erosion and sediment yield were observed in October-November and April-May, with the lowest rates in August and December. Observed sediment values were often lower than estimated values. Validating empirical model results for erosion and sediment estimation solely based on observational data is insufficient; detailed analysis of measured erosion data is necessary for comprehensive validation.